The Strategy for Economic Structural Reforms and Innovation Development of Ukraine - Kurza, Yu.P. (Science and Innovation, 2024)
The economic, scientific, technological, and innovative status of Ukraine and the government policy in this area have been analyzed from the standpoint of scientific, technological, competitive gap and technology (innovation) negotiability. A strategy to create a new diversified innovative economy through scientific and technological transfer from international companies which are the world technological leaders has been proposed.